2019
DOI: 10.1080/14756366.2019.1618292
|View full text |Cite
|
Sign up to set email alerts
|

Seeking new approach for therapeutic treatment of cholera disease via inhibition of bacterial carbonic anhydrases: experimental and theoretical studies for sixteen benzenesulfonamide derivatives

Abstract: Capasso (2019) Seeking new approach for therapeutic treatment of cholera disease via inhibition of bacterial carbonic anhydrases: experimental and theoretical studies for sixteen benzenesulfonamide derivatives,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…38 In detail, we used the crystal structure of the dimeric (chains A and B) VchCAβ retrieved from the Protein Data Bank (PDB Code: 5CXK), 10 that has been "modeled" in open conformation on the basis of β-CA from the green algae Coccomyxa 24 (PDB Code: 3UCJ) as previously reported and shown in Figure 2 for AAZ. 14 The docking results confirmed that N-(4-sulfamoylbenzyl)amide derivatives 20a−i adopted the canonical orientation of sulfonamide-based CAIs for which for the deprotonated form of the sulfonamide moiety is anchored to the zinc ion coordinated by residues Cys42, His98, and Cys101 (chain A, colored in blue). As expected, the aromatic ring of the benzenesulfonamide portion is stabilized through a π−π interaction with Tyr83 (chain B, colored in wheat).…”
mentioning
confidence: 99%
“…38 In detail, we used the crystal structure of the dimeric (chains A and B) VchCAβ retrieved from the Protein Data Bank (PDB Code: 5CXK), 10 that has been "modeled" in open conformation on the basis of β-CA from the green algae Coccomyxa 24 (PDB Code: 3UCJ) as previously reported and shown in Figure 2 for AAZ. 14 The docking results confirmed that N-(4-sulfamoylbenzyl)amide derivatives 20a−i adopted the canonical orientation of sulfonamide-based CAIs for which for the deprotonated form of the sulfonamide moiety is anchored to the zinc ion coordinated by residues Cys42, His98, and Cys101 (chain A, colored in blue). As expected, the aromatic ring of the benzenesulfonamide portion is stabilized through a π−π interaction with Tyr83 (chain B, colored in wheat).…”
mentioning
confidence: 99%
“…The two subsets of 2-(hetero)arylformamido-N-(4sulfamoylphenyl)alkylamides and (hetero)arylformamido-N-[(4sulfamoylphenyl]methyl)alkylamides were synthesized by means of a multi-step process. All new synthesized compounds were screened for their potential CA inhibitory property against VchCAα, VchCAβ, and VchCAγ and Ki values were compared to the off-target human CA I and CA II, thus furnishing suggestions [12] and 4-(4-cyano-4-phenylpiperidine-1-carbonyl)benzenesulfonamide (4) [22] . (1-cyano-2-ethoxy-2-oxoethylidenaminooxy) dimethylaminomorpholinocarbenium hexafluorophosphate) (COMU).…”
Section: Design and Synthesismentioning
confidence: 99%
“…Among this series of compounds, the best outcome was obtained for the 4-(4-cyano-4-phenyl-piperidine-1carbonyl)benzenesulfonamide ( 4), which combined nanomolar activity against VchCAα (K i = 89.9 nM) with sub-micromolar affinity against VchCAβ (K i = 806.4 nM). [22] From the structural data collected for these three classes of bacterial CAs, we might observe that VchCAβ and VchCAγ possess a narrower active site (Figure 2) when compared with VchCAα; [23] therefore, the different structural organization might explain the different degree of affinity/inhibition measured for several studied compounds bearing the sulfonamide pharmacophore linked to bulky groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the benzenesulfonamide moiety has been extensively explored as a crucial binding motif for the CA active site cavity close to the zinc ion . To improve the isoform selectivity of CAIs, efforts have been generally addressed to introduce an additional fragment linked to benzenesulfonamide as a “tail” for enhancing the interaction with hydrophobic/hydrophilic residues paving the middle and/or top region of the active site cavity. ,,, …”
mentioning
confidence: 99%